2004
DOI: 10.1159/000076365
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Cardiac Troponin T and Troponin I Levels in Multiple-Gestation Neonates

Abstract: The increased mortality and morbidity rates in multiple-gestation neonates are not completely understood. Troponin measurements have a role in situations where the evaluation of the cardiac damage is difficult, such as in cases of unexplained intrauterine fetal growth restriction or death. These conditions, along with perinatal hypoxic risk and in utero ischemic damage, are frequently found in multiple gestations. In this context, a myocardial damage could be expected more frequently in multiple than in single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Similar to Trevisanuto et al [10], we found cTnI levels !1 ng/ml in the cord blood, 3rd and 7th day serum of healthy newborns similar to healthy adults. Studies about cTnI levels in neonates is limited [10,11,[33][34][35]. Engin et al [35] found increased cord cTnI levels in newborns with maternal hypertensive disorders, magnesium sulfate exposure and preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Trevisanuto et al [10], we found cTnI levels !1 ng/ml in the cord blood, 3rd and 7th day serum of healthy newborns similar to healthy adults. Studies about cTnI levels in neonates is limited [10,11,[33][34][35]. Engin et al [35] found increased cord cTnI levels in newborns with maternal hypertensive disorders, magnesium sulfate exposure and preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Trevisanuto et al [10] studied cord blood cTnI and cTnT in healthy newborns and they found undetectable levels as adults. A recent study [11] investigated elevation of cTnT and cTnI in multiple-gestation neonates as possible indicators of myocardial damage to detect ischemia in utero. The results showed normal levels of both of these proteins in twins at birth and no difference was found between the first-and the second-born twins.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are frequently found in multiple gestations. However, in previous study troponins T and I and creatine kinase MB concentrations were not increased in twins at birth and were not different between the first-and the second-born twin [41]. These data suggested that myocardial damage, evaluated by cardiac troponin T, troponin I, and creatine kinase MB measurements, does not seem to be a relevant problem in multiple-gestation neonates.…”
Section: Cardiac Troponin In Cord Bloodmentioning
confidence: 68%
“…In multiple gestations, troponins T and I and CK-MB were not increased in twins at birth and were not different between the first-and the second-born twin [62]. In intrauterine growth restriction that implies foetal hypoxia, resulting in flow redistribution and sparing of vital organs, no differences in troponin I levels were observed between the appropriate-for-gestational-age and intrauterine growth restriction groups [63].…”
Section: Cardiac Injury Biomarkers In the Cord Bloodmentioning
confidence: 84%